Oxidation-influenced crystallization in (GeSe2)(x)(Sb2Se3)(1-x) chalcogenide glasse - Svoboda, Roman (Elsevier Science BV, 2019)
Influence of oxygen atmosphere on crystallization of (GeSe(2))(x)(Sb2Se3)(1-x) glasses (for x = 0.3, 0.4 and 0.5) was investigated by differential scanning calorimetry, X-ray diffraction analysis and infrared microscopy. Particlesize-dependent study was performed to reveal the role of mechanically induced defects. The presence of oxygen led to an early formation of a thin surface crystalline layer (smoothly structured) that significantly influenced further crystal growth. The most pronounced consequence was surprisingly found in case of the (GeSe2)(0.3)(Sb2Se3)(0.7) composition that crystallizes in volume. The thin surface crystalline layer hindered the macroscopic viscous flow, so that the samples retained their original shape, and these quasi-stationary conditions accelerated the initial nucleation and growth rates. At the same time, however, these conditions prevented the samples from reaching full crystallinity. In case of the compositions with x = 0.4 and 0.5, the crystal growth proceeded only at the surface and presence of external interfaces and mechanically induced defects took over the major role driving the crystallization kinetics. Correlation of the calorimetric, microscopic and viscosity data is discussed in detail.
Oxidací ovlivněná krystalizace v (GeSe2)(x)(Sb2Se3)(1-x) chalcogenidových sklech
Keywords: Crystallization behavior; Oxygen atmosphere; DSC; XRD; Infrared microscopy; (GeSe(2))(x)(Sb2Se3)(1-x) glasses; krystalizace; kyslíková atmosféra; DSC; XRD; mikroskopie; Ge-Sb-Se skla